Les nouveaux espaces publics chez les Yucuna d’Amazonie colombienne - Laurent Fontaine (Journal de la Société des Américanistes)
Since the beginning of the twentieth century, the regular contacts of the Yucuna Indians with some new external actors have gradually led them to experience new public spaces, permanently transforming their social organization. This article reviews the history of these spaces. The analysis of traditional gathering areas shows that they are distinguishable from modern public spaces. It is only with the entrance of the rubber exploiters, state officials and missionaries, that the Yucuna communities were forced to open up to the surrounding society. The 1970’s were then marked by the emergence of the indigenous assemblies that are probably the areas of interaction which are the most representative of modern public spaces integrated in communities.